THE IMPACT OF INTERNAL AUDIT AND CREDIT POLICY ON NON-PERFORMING LOANS IN COOPERATIVES - Lindasari Lindasari; Rahmawati Rahmawati; Abid Ramadhan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
Ideologically, the biggest problem for the Indonesian nation is building an economic system that is in accordance with the ideals of mutual cooperation. The answer to the ideological question is that cooperatives are an economic basis based on mutual cooperation ideals. Cooperatives prioritize common interests and subordinate individual interests. Cooperatives therefore must have a mandate to grow the community to look after the common interest. The method used is descriptive research method, because this research aims to get answers to opinions, responses or observations, so the discussion must be qualitative in nature or use descriptive words. "Descriptive research tries to find adequate and precise descriptions of all activities, objects, processes, and people." (Sulistyo-Basuki, 2010:110). Its nature is only to provide information by collecting information from various sources, namely literature, magazines, expert opinions, books and other sources. In South Sulawesi alone there are 4,535 active cooperative units, one of which is located in the city of Palopo which has several active cooperatives.